Analysis of the efficacy of triple-channel minimally invasive knee arthroscopy in treating popliteal cysts in children - Yongwei Zhou; Qining Yang; Jiayu Kang; Shan He (BMC Surgery)
Abstract Background This study aimed to investigate a technique for treating pediatric popliteal cysts with a triple-channel knee arthroscopic approach, hypothesizing that this technique exhibits favorable clinical outcomes with reduced recurrence rates. Methods A retrospective analysis was conducted on the clinical data of 14 patients with symptomatic pediatric popliteal cysts admitted to the joint surgery center using an arthroscopic minimally invasive technique from December 2017 to December 2020. Arthroscopy was employed for adequate enlargement of the posterior medial flap opening between the cyst and the joint cavity and to completely resect the cyst wall. The popliteal cyst recurrence was assessed through Magnetic Resonance Imaging(MRI) at 3 and 12 months post-surgery, and the Rauschning and Lindgren scores were recorded to evaluate the clinical prognosis. Results A total of 14 children completed the follow-up, including 8 boys and 6 girls, with a mean age of 9.9 ± 1.1 years (5–12 years); 5 cases in the left knee and 9 cases in the right knee; the mean operative time was 19.2 ± 2.7 min (10–25 min); and the mean follow-up time was 15.1 ± 2.4 months (12–24 months). There was no intraoperative vascular or nerve injury and no incisional exudate infection. Postoperatively, posterior knee symptoms disappeared in the children, Rauschning and Lindgren scores significantly improved, and no recurrence signs were observed on MRI. Conclusions This study determined that the arthroscopic three-channel minimally invasive technique is effective and safe for treating popliteal cysts in children, making it worthy of clinical promotion.